Dilute Sb Doping Yields Softer p‐Type Bi2Te3 Thermoelectrics - Hung‐Wei Chen; Bo‐Chia Chen; Hsin‐Jay Wu (Advanced Electronic Materials, 2024)
Abstract In this study, the Sb content within p‐type Bi2Te3 by employing phase diagram engineering is strategically tuned. This method retains the advantages of Sb doping but mitigated the brittleness typically seen in high‐Sb Bi0.5Sb1.5Te3 (BST). The as‐constructed phase diagram demonstrates the asymmetrical homogeneity of (Bi, Sb)2Te3, guiding focus toward developing an optimized p‐type (Bi2Te3)0.96(Sb2Te)0.04 with reduced Sb content. The resulting crystal of (Bi2Te3)0.96(Sb2Te)0.04 exhibit an exceptional peak zT of 1.3 at 303 K, surpassing the mechanical robustness of standard high‐Sb BST. Additionally, it matches the energy conversion efficiency of traditional BST, achieving 2.3% at a temperature difference ΔT of 150 K. This significant advance makes (Bi2Te3)0.96(Sb2Te)0.04 a potential competitor to the well‐established BST, thanks to its enhanced thermoelectric performance owing to the elevated carrier concentration and a less brittle nature due to the diluted Sb dopant.